Positive electrode active material for lithium secondary battery, method for producing the same, and lithium secondary battery including the same

The development of secondary particles formed by aggregating primary giant particles with specific size and density, coated with boron-containing substances, addresses the stability and performance issues of conventional lithium cobalt oxide-based materials, enhancing life and resistance characteristics.

JP7623486B2Active Publication Date: 2025-01-28LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023531687
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-25
Filing Date
2021-11-25
Publication Date
2025-01-28
Estimated Expiration
2041-11-25

AI Technical Summary

Technical Problem

Conventional lithium cobalt oxide-based positive active materials face challenges due to high cobalt prices, supply instability, and issues with particle strength, leading to increased gas generation, reduced cycle performance, and inferior structural and chemical stability, especially in high-nickel compositions.

Method used

Development of a positive electrode active material comprising secondary particles formed by the aggregation of primary giant particles with specific size and crystal density, coated with boron-containing substances, to enhance particle strength and stability.

Benefits of technology

The solution provides a positive electrode active material with improved life characteristics and resistance characteristics by minimizing particle cracks and securing a stable lithium-ion pathway, resulting in enhanced performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623486000004
    Figure 0007623486000004
  • Figure 0007623486000005
    Figure 0007623486000005
  • Figure 0007623486000001
    Figure 0007623486000001
Patent Text Reader

Abstract

The present invention relates to a cathode active material including at least one secondary particle comprising an aggregate of primary macroparticles, a method for producing the same, and a lithium secondary battery including the same. According to one aspect of the present invention, a cathode active material including secondary particles having improved resistance due to growth in crystal size simultaneously with growth in the average particle size (D50) of the primary macroparticles can be provided. According to another aspect of the present invention, a cathode active material with increased true density can be provided. This allows for secure lithium ion migration paths and minimizes defects in the crystalline structure of the cathode active material, thereby providing a nickel-based cathode active material with improved life and resistance characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, which contains primary large particles, and a method for producing the same.

[0002] This application claims priority to Korean Patent Application No. 10-2020-0159518, filed on November 25, 2020, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] In recent years, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have relatively high capacity has been rapidly increasing. In particular, lithium secondary batteries are lightweight and have high energy density, and are in the spotlight as a driving power source for portable devices. Therefore, research and development to improve the performance of lithium secondary batteries has been actively conducted.

[0004] A lithium secondary battery generates electrical energy by oxidation and reduction reactions occurring when lithium ions are inserted / deintercalated at the positive and negative electrodes, with an organic or polymer electrolyte filled between the positive and negative electrodes, which are made of active materials capable of intercalating and deintercalating lithium ions.

[0005] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compound (LiFePO4), etc. are used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its advantages of high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage. However, due to the rising price of cobalt (Co) and unstable supply, there are limitations to its large-scale use as a power source in fields such as electric vehicles, and there is a demand for the development of an alternative positive electrode active material.

[0006] Therefore, nickel-cobalt-manganese-based lithium composite transition metal oxides (hereinafter simply referred to as "NCM-based lithium composite transition metal oxides") have been developed in which part of the cobalt (Co) is replaced with nickel (Ni) and manganese (Mn).

[0007] Meanwhile, the previously developed NCM-based lithium transition metal composite oxide is in the form of secondary particles formed by agglomeration of primary micro particles, and has a large specific surface area and low particle strength. In addition, when rolling an electrode after manufacturing it, cracks in the secondary particles cause a large amount of gas generation during cell operation, leading to poor cycle performance and reduced stability. In particular, in the case of a high-nickel (Ni) NCM-based lithium transition metal composite oxide in which the nickel (Ni) content is increased to ensure high capacity, structural and chemical stability is further reduced, and thermal stability is also difficult to ensure. Summary of the Invention [Problem to be solved by the invention]

[0008] The problem to be solved by the present invention is to provide a positive electrode active material that includes primary giant particles unlike conventional ones, while having the same or similar average particle size (D50) as conventional ones, thereby minimizing particle cracking during rolling of the positive electrode active material.

[0009] Another object of the present invention is to provide a positive electrode active material with increased true density (crystal density).

[0010] Thus, it is an object of the present invention to provide a positive electrode active material having improved life characteristics and resistance characteristics. [Means for solving the problem]

[0011] An aspect of the present invention provides a positive electrode active material according to the following embodiment.

[0012] Specifically, the at least one secondary particle comprises an agglomerate of a primary macroparticle, The primary macroparticles have an average particle size (D50) of 2 μm or more; The ratio of the average particle size (D50) of the primary macroparticles to the average crystal size of the primary macroparticles is 8 or more; The secondary particles have an average particle size (D50) of 3 μm to 10 μm, and the true density (crystal density) of the secondary particles is 4.74 or more.

[0013] In the positive electrode active material for a lithium secondary battery, the primary macroparticles may have an average crystal size of 200 nm or more.

[0014] The positive electrode active material for a lithium secondary battery may have a ratio of an average particle size (D50) of the secondary particles to an average particle size (D50) of the primary large particles of 2-4.

[0015] In the positive electrode active material for a lithium secondary battery, the secondary particles may contain a nickel-based lithium transition metal oxide.

[0016] The positive electrode active material for lithium secondary batteries is a nickel-based lithium transition metal oxide. a Ni 1-x-y Co x M1 y M2 w O2 (1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M1 is at least one selected from the group consisting of Mn and Al, and M2 is at least one selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo).

[0017] The positive electrode active material for a lithium secondary battery may include at least one of zirconium, yttrium, and strontium as a sintering additive.

[0018] The positive electrode active material for a lithium secondary battery may have a surface coated with a boron-containing material.

[0019] The positive electrode active material for a lithium secondary battery may have a cobalt-containing material coated on a surface of the positive electrode active material.

[0020] Another aspect of the present invention provides a positive electrode for a lithium secondary battery, comprising the above-described positive electrode active material.

[0021] Yet another aspect of the present invention provides a lithium secondary battery including the above-described positive electrode active material.

[0022] Yet another aspect of the present invention provides a method for producing a positive electrode active material.

[0023] Specifically, the method includes the steps of: (S1) mixing a nickel-based transition metal oxide precursor having a tap density of 2.0 g / cc or less with a lithium precursor and primarily firing the mixture; (S2) subjecting the first-fired product to a second firing, The method for preparing a positive electrode active material for a lithium secondary battery includes at least one secondary particle including an aggregate of a primary macro particle through the primary and secondary firing, The primary macroparticles have an average particle size (D50) of 2 μm or more; The ratio of the average particle size (D50) of the primary macroparticles to the average crystal size of the primary macroparticles is 8 or more; The secondary particles have an average particle size (D50) of 3 μm to 10 μm, and a true density (crystal density) of 4.74 or more.

[0024] In the method for producing a positive electrode active material for a lithium secondary battery, the primary baking may be performed at a temperature of 780°C to 900°C. Effect of the Invention

[0025] According to one aspect of the present invention, it is possible to provide a positive electrode active material including secondary particles having improved resistance due to the growth of the average particle size (D50) of the primary large particles and the growth of the crystal size at the same time.

[0026] According to one aspect of the present invention, a positive electrode active material having an increased true density can be provided, which can provide a lithium ion migration path and minimize defects in the crystal structure of the positive electrode active material, thereby providing a nickel-based positive electrode active material having improved life and resistance characteristics.

[0027] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0028] [Figure 1] 1 is a graph showing capacity retention and resistance according to an embodiment of the present invention and a comparative example. [Diagram 2] 1 is a graph showing resistance and SOC according to an embodiment and a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, the embodiment of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the configurations shown in the embodiments described in this specification are merely the most preferred embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of this application.

[0030] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.

[0031] In the present specification and claims, "comprising a large number of crystal grains" means a crystal consisting of two or more crystal grains having an average crystal size in a specific range. In this case, the crystal size of the crystal grains can be quantitatively analyzed using X-ray diffraction analysis (XRD) using CuKα X-rays (Xrα). Specifically, the average crystal size of the crystal grains can be quantitatively analyzed by placing the produced particles in a holder and analyzing the diffraction pattern produced by irradiating the particles with X-rays.

[0032] In this specification and claims, D50 may be defined as the particle size at 50% of the particle size distribution and may be measured using the laser diffraction method.

[0033] In the present invention, the term "primary particles" refers to particles that have no apparent grain boundaries when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope.

[0034] In the present invention, the "secondary particles" refer to particles formed by agglomeration of the primary particles.

[0035] In the present invention, the term "single particle" refers to a particle that exists independently of the secondary particles and has no apparent grain boundaries, for example, a particle having a particle size of 1 μm or more.

[0036] In the present invention, the term "particle" may mean any one or all of a single particle, a secondary particle, and a primary particle.

[0037] <Cathode active material> One aspect of the present invention provides a positive electrode active material having a secondary particle form different from that of the conventional one.

[0038] in particular, 1) comprises at least one secondary particle comprising an aggregate of a primary macroparticle; 2) The primary macroparticles have an average particle size (D50) of 2 μm or more; 3) the ratio of the average particle size (D50) of the primary macroparticles to the average crystal size of the primary macroparticles is 8 or more; 4) The average particle size (D50) of the secondary particles is 3 to 10 μm, 5) The positive electrode active material for a lithium secondary battery, wherein the secondary particles have a true density (crystal density) of 4.74 or more.

[0039] The primary particles and secondary particles have the above characteristics 1) to 5), making it possible to provide a nickel-based positive electrode active material with improved life characteristics and resistance characteristics.

[0040] The characteristics 1) to 5) of the primary particles and secondary particles will be described in detail below.

[0041] <Particle morphology and primary macroparticles> In general, the nickel-based lithium transition metal oxide is in the form of secondary particles, which may be in the form of aggregates of primary particles.

[0042] Specifically, dense nickel-based lithium transition metal hydroxide secondary particles prepared by a coprecipitation method are used as a precursor, and the precursor is mixed with a lithium precursor and sintered at a temperature of less than 960° C. to obtain nickel-based lithium transition metal oxide secondary particles. However, when a cathode active material including such conventional secondary particles is applied to a current collector and then rolled, the particles themselves crack, increasing the specific surface area. If the specific surface area is increased, a rock salt structure is formed on the surface, resulting in high resistance.

[0043] In order to solve these problems, a positive electrode active material made of single particles has been developed. Specifically, unlike the conventional method of using the dense nickel-based lithium transition metal hydroxide secondary particles as a precursor, a precursor that is more porous than the conventional precursor is used, which allows synthesis at a lower firing temperature compared to the same nickel content, and a nickel-based lithium transition metal oxide that is not in the form of secondary particles and is made into a single particle can be obtained. However, when a positive electrode active material containing such single particles is applied to a current collector and then rolled, the single particles themselves do not crack, but other active materials may crack.

[0044] One aspect of the present invention is to solve such problems.

[0045] When a high-density precursor is fired at a high firing temperature as in the past, it is inevitable that not only the average particle size (D50) of the primary particles but also the average particle size (D50) of the secondary particles will increase.

[0046] Meanwhile, the secondary particles according to one embodiment of the present invention are different from the conventional single particle obtaining method in the following points.

[0047] As described above, conventional single particles are formed by simply increasing the primary firing temperature using a conventional precursor for secondary particles. On the other hand, secondary particles according to one embodiment of the present invention use a separate precursor with high porosity. As a result, primary large particles with large diameters can be grown without increasing the firing temperature, while secondary particles grow relatively insufficiently compared to conventional methods.

[0048] As a result, the secondary particles according to one embodiment of the present invention have the same or similar average particle size (D50) as conventional ones, but the average particle size (D50) of the primary particles is large. That is, unlike the general form of conventional positive electrode active materials, that is, a form in which primary particles having a small average particle size are aggregated to form secondary particles, the secondary particles according to one embodiment of the present invention provide a form in which primary large particles are aggregated to form large primary particles.

[0049] Specifically, the secondary particles according to one aspect of the present invention refer to aggregates of primary giant particles. In one specific embodiment of the present invention, the secondary particles may be aggregates of 1 to 10 primary giant particles. More specifically, the secondary particles may be aggregates of 1 or more, 2 or more, 3 or more, or 4 or more primary giant particles within the above numerical range, and may be aggregates of 10 or less, 9 or less, 8 or less, or 7 or less primary giant particles within the above numerical range.

[0050] In the present invention, "primary large particles" are those having a mean particle size (D50) of 2 μm or more.

[0051] In a specific embodiment of the present invention, the primary large particles may have an average particle size of 2 μm or more, 2.5 μm or more, 3 μm or more, or 3.5 μm or more, and may have an average particle size of 5 μm or less, 4.5 μm or less, or 4 μm or less. If the average particle size of the primary large particles is less than 2 μm, they correspond to conventional secondary particles, and there may be a problem of particle cracking during rolling.

[0052] Meanwhile, in the present invention, the "primary giant particles" have a ratio of average particle diameter (D50) to average crystal size of 8 or more. That is, compared with primary microparticles constituting conventional secondary particles, the primary giant particles are primary particles in which the average particle diameter and average crystal size have grown simultaneously.

[0053] From the viewpoint of cracks, it is advantageous to have a large average particle size while having no grain boundaries in appearance like conventional single particles. Therefore, the inventors focused on growing the average particle size (D50) of the primary particles. In the process, they found that if only the average particle size (D50) of the primary particles is increased by over-firing, a rock salt structure is formed on the surface of the primary particles, resulting in high initial resistance. To solve this problem, the inventors devised a method to reduce resistance and confirmed that in order to reduce resistance, the crystal size of the primary particles must also be grown.

[0054] Therefore, the primary large particles in the present invention refer to particles that have a large average crystal size as well as a large average grain size and have no apparent grain boundaries.

[0055] When the average particle size and average crystal size of the primary particles grow simultaneously in this manner, the resistance is lowered and it has the advantage of a longer life, compared to conventional single particles, which have a large increase in resistance due to a rock salt structure formed on the surface when fired at high temperatures.

[0056] In this case, the average crystal size of the primary giant particles can be quantitatively analyzed by X-ray diffraction analysis (XRD) using CuKα X-rays. Specifically, the average crystal size of the primary giant particles can be quantitatively analyzed by placing the produced particles in a holder, irradiating the particles with X-rays, and analyzing the diffraction pattern produced.

[0057] In a specific embodiment of the present invention, the ratio of the average particle diameter (D50) to the average crystal size is 8 or more, preferably 10 or more.

[0058] Additionally, the average crystal size of the primary macroparticles may be 200 nm or more, 250 nm or more, or 300 nm or more.

[0059] <Secondary particles> The secondary particles according to one embodiment of the present invention have the same or similar average particle size (D50) as conventional ones, but have a large average particle size (D50) of primary particles. That is, unlike the general form of conventional positive electrode active materials, that is, a form in which primary particles having a small average particle size are aggregated to form secondary particles, the secondary particles are provided in the form of agglomeration of primary giant particles that are enlarged primary particles.

[0060] The secondary particles according to one embodiment of the present invention have an average particle size (D50) of 3 μm to 10 μm. More specifically, it may be 4 μm to 8 μm, and may be 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, or 6 μm or more, and may be 8 μm or less, 7.5 μm or less, 7 μm or less, or 6.5 μm or less.

[0061] Generally, regardless of particle morphology, if the composition is the same, the particle size and the average crystal size within the particle increase as the sintering temperature increases. Meanwhile, in the secondary particles according to one embodiment of the present invention, primary large particles having a large diameter can grow without increasing the sintering temperature compared to the conventional method, while the secondary particles grow relatively insufficiently compared to the conventional method.

[0062] As a result, the secondary particles according to one embodiment of the present invention are composed of primary macroparticles having a larger average particle size and average crystal size than conventional primary fine particles, while having the same or similar average particle size (D50) as conventional secondary particles.

[0063] For example, it may include secondary particles having an average particle size (D50) of about 5 μm, which are formed by agglomerating up to 10 primary giant particles having an average particle size (D50) of about 2.5 μm. These secondary particles are characterized by the fact that they do not crack when the positive electrode active material is rolled, and that cracks are minimized when the positive electrode active material is mixed (blended) with other particles and rolled.

[0064] More specifically, when at least one of the secondary particles is rolled at 9 tons, the primary large particles fall off, but the primary particles themselves do not crack.

[0065] As a result, in the positive electrode active material according to one embodiment of the present invention, the content of fine particles having a size of 1 μm or less is less than 10% after rolling at 9 tons.

[0066] In a specific embodiment of the present invention, the ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary macroparticles may be 2-4.

[0067] On the other hand, the secondary particles according to the present invention have a true density (crystal density) of 4.74 or more.

[0068] The present inventors have conducted extensive research to simultaneously improve the life and resistance characteristics of positive electrode active materials, and have found that even if the average particle size and crystal size of primary macroparticles are increased, differences in electrochemical performance may occur in some cases.

[0069] As a result of extensive research to solve these problems, the inventors have surprisingly found that a positive electrode active material with improved life characteristics and resistance characteristics can be provided by simultaneously controlling the average particle size and crystal size of primary particles and the true density of secondary particles.

[0070] In a specific embodiment of the present invention, the true density of the secondary particles may be 4.74 or more, 4.77 or more, or 4.78 or more, and may be 4.80 or less.

[0071] <Composition> The secondary particles may include a nickel-based lithium transition metal oxide.

[0072] In this case, the nickel-based lithium transition metal oxide is Li a Ni 1-x-y Co x M1 y M2 w O2 (1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M1 is at least one selected from the group consisting of Mn and Al, and M2 is at least one selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo).

[0073] In the above formula, a, x, y, and w represent the molar ratios of each element in the nickel-based lithium transition metal oxide.

[0074] In this case, the metals M1 and M2 doped into the crystal lattice of the secondary particle may be located only on a portion of the surface of the particle, or may be located with a concentration gradient that decreases from the surface toward the center of the particle, or may be uniformly present throughout the particle, depending on the positional preference of the element M1 and / or the element M2.

[0075] When the secondary particles are doped or coated and doped with metals M1 and M2, the long life characteristics of the active material can be further improved, particularly due to stabilization of the surface structure.

[0076] The positive electrode active material may be coated on its surface with a boron-containing material such as lithium boron oxide, and the boron content may be, for example, 2,000 ppm or less. Methods for coating the boron-containing material are well known in the art.

[0077] The positive electrode active material may be coated on its surface with a cobalt-containing material such as lithium cobalt oxide, and the cobalt content may be, for example, 20,000 ppm or less. Methods for coating the cobalt-containing material are well known in the art.

[0078] <Method of manufacturing positive electrode active material> The positive electrode active material according to an embodiment of the present invention may be prepared by the following method, but is not limited thereto.

[0079] Specifically, the method includes: (S1) mixing a nickel-based transition metal oxide precursor having a tap density of 2.0 g / cc or less with a lithium precursor and subjecting the mixture to primary firing; and (S2) subjecting the primary firing product to secondary firing, Through the primary and secondary firing, a positive electrode active material for a lithium secondary battery including at least one secondary particle including an aggregate of primary macroparticles is manufactured.

[0080] The method for preparing the positive electrode active material will now be described step by step.

[0081] First, a positive electrode active material precursor containing nickel (Ni), cobalt (Co) and manganese (Mn) and having a tap density of 2.0 g / cc or less is prepared.

[0082] In this case, the precursor for producing the positive electrode active material may be a commercially available positive electrode active material precursor, or may be produced by a method for producing a positive electrode active material precursor known in the art.

[0083] For example, the precursor may be prepared by adding an ammonium cation-containing chelating agent and a basic compound to a transition metal solution containing a nickel-containing source material, a cobalt-containing source material, and a manganese-containing source material, and then subjecting the mixture to a coprecipitation reaction.

[0084] The nickel-containing source material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salts, nickel halides, or combinations thereof.

[0085] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and may be, but is not limited to, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof.

[0086] The manganese-containing source material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically, manganese oxide such as Mn2O3, MnO2, Mn3O4, etc.; manganese salt such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0087] The transition metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, or may be prepared by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and the manganese-containing raw material.

[0088] The ammonium cation-containing chelating agent may be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3, or a combination thereof, but is not limited thereto. Meanwhile, the ammonium cation-containing chelating agent may be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.

[0089] The basic compound may be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. The basic compound may also be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, an alcohol, etc.) that is uniformly miscible with water.

[0090] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount such that the pH of the metal solution becomes 9 to 11.

[0091] Meanwhile, the coprecipitation reaction may be carried out in an inert atmosphere such as nitrogen or argon at a temperature of 40°C to 70°C.

[0092] Through the above process, nickel-cobalt-manganese hydroxide particles are produced and precipitated in the reaction solution. By adjusting the concentrations of the nickel-containing raw material, the cobalt-containing raw material, and the manganese-containing raw material, a precursor having a nickel (Ni) content of 60 mol% or more in the total metal content can be produced. The precipitated nickel-cobalt-manganese hydroxide particles can be separated and dried by a conventional method to obtain a nickel-cobalt-manganese precursor. The precursor can be secondary particles formed by agglomeration of primary particles.

[0093] Thereafter, the precursor and the lithium source material are mixed and primarily baked.

[0094] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it is soluble in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of these may be used.

[0095] In the case of a high-nickel (high-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 60 mol % or more, the primary firing may be performed at 700° C. to 1,000° C., more preferably 780° C. to 980° C., and even more preferably 780° C. to 900° C. The primary firing may be performed in an air or oxygen atmosphere for 10 hours to 35 hours.

[0096] Then, after the primary firing, an additional secondary firing may be performed.

[0097] In the case of a high-nickel (high-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 60 mol % or more, the secondary firing may be performed at 650° C. to 800° C., more preferably 700° C. to 800° C., and even more preferably 700° C. to 750° C. The secondary firing may be performed in an air or oxygen atmosphere, and cobalt oxide or cobalt hydroxide may be added at 20,000 ppm during the secondary firing.

[0098] Meanwhile, the present invention is characterized in that no separate water washing step is included between the steps (S1) and (S2).

[0099] Through these steps, a positive electrode active material having secondary particle aggregates containing primary giant particles can be produced.

[0100] <Positive electrodes and lithium secondary batteries> According to yet another aspect of the present invention, there is provided a positive electrode for a lithium secondary battery, and a lithium secondary battery, each of which includes the positive electrode active material.

[0101] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0102] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0103] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material described above.

[0104] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may usually be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0105] In addition, the binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0106] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode may be manufactured by coating a composition for forming a positive electrode active material layer, which includes the positive electrode active material and, optionally, a binder and a conductive material, on a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0107] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into consideration the coating thickness of the slurry and the manufacturing yield, and to provide a viscosity that allows excellent thickness uniformity to be achieved when the slurry is applied to manufacture a positive electrode.

[0108] Alternatively, the positive electrode may be manufactured by casting the composition for forming a positive electrode active material layer on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0109] According to yet another aspect of the present invention, there is provided an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0110] The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0111] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0112] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to increase the adhesive strength of the negative electrode active material, as in the case of the positive electrode current collector. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0113] The negative electrode active material layer may include a negative electrode active material and, optionally, a binder and a conductive material, and may be manufactured, for example, by coating a negative electrode forming composition including a negative electrode active material and, optionally, a binder and a conductive material on a negative electrode current collector and drying the composition, or by casting the negative electrode forming composition on a separate support and then peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0114] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon may be used as the carbonaceous material. Representative low-crystalline carbons include soft carbon and hard carbon, and representative high-crystalline carbons include amorphous, plate-like, scaly, spherical, or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal-based coke.

[0115] Additionally, the binder and conductive material are the same as those described above for the positive electrode.

[0116] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0117] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0118] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0119] The organic solvent may be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move.Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), or propylene carbonate (PC); an alcohol solvent such as ethyl alcohol or isopropyl alcohol; a nitrile such as R-CN (R is a hydrocarbon group having a linear, branched, or cyclic structure of C2 to C20, and may contain a double bond aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; or a sulfolane. Among them, carbonate-based solvents are preferable, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant capable of improving the charge / discharge performance of a battery and a low-viscosity linear carbonate-based compound (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is more preferable. In this case, it is preferable to mix the cyclic carbonate and the linear carbonate in a volume ratio of about 1:1 to about 1:9 for excellent electrolyte performance.

[0120] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt may be within a range of 0.1 to 2.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore exhibits excellent electrolyte performance and allows lithium ions to move effectively.

[0121] In addition to the electrolyte components described above, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving battery life characteristics, suppressing a decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.

[0122] A lithium secondary battery containing the positive electrode active material according to the present invention is useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).

[0123] According to yet another aspect of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0124] The battery module or battery pack may be used as a power source for one or more medium to large devices including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.

[0125] The present invention will now be described in detail with reference to exemplary embodiments so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments described below.

[0126] <Example 1> (Production of positive electrode active material) Nickel-cobalt-manganese hydroxide (Ni 0.86 Co 0.07 Mn 0.07 The (OH)2) cathode active material precursor and lithium source material LiOH were put into a Henschel mixer (700L) so that the final Li / M (Ni, Co, Mn) molar ratio was 1.01, and mixed for 20 minutes at 300 rpm in the center. The mixed powder was placed in an alumina crucible measuring 330mm x 330mm, and primary fired at 900℃ for 10 hours in an oxygen (O2) atmosphere to form a primary fired product.

[0127] Thereafter, the primary fired product was pulverized using a jet mill at a feeding pressure of 80 psi and a grinding pressure of 60 psi.

[0128] The crushed primary fired material was placed in an alumina crucible measuring 330 mm x 330 mm, and 10,000 ppm of Co(OH)2 was added in an oxygen (O2) atmosphere, followed by secondary firing at 700°C for 5 hours to produce a positive electrode active material.

[0129] <Example 2> A positive electrode active material was produced in the same manner as in Example 1, except that the tap density of the precursor was set to 1.5 g / cc, the primary firing temperature was lowered to 20° C., LiOH was added to a Henschel mixer (700 L) so that the final Li / M (Ni, Co, Mn) molar ratio was 1.05, and 0.02 mol% Li was further added during the secondary coating.

[0130] <Comparative Example> After 4 liters of distilled water was put into a coprecipitation reactor (volume 20 L), 100 mL of 28 wt% aqueous ammonia solution was added while maintaining the temperature at 50 ° C. Then, a 3.2 mol / L transition metal solution, which was a mixture of NiSO4, CoSO4, MnSO4, and Al3(SO4)2 so that the molar ratio of nickel:cobalt:manganese:aluminum was 82:5:11:2, was continuously added to the reactor at 300 mL / hr and 28 wt% aqueous ammonia solution at 42 mL / hr. The mixture was stirred at an impeller speed of 400 rpm, and a 40 wt% sodium hydroxide solution was added to maintain the pH at 11.0. The mixture was co-precipitated for 24 hours to form precursor particles. The precursor particles were separated and washed, and then dried in an oven at 130 ° C to produce a precursor.

[0131] Ni synthesized by coprecipitation reaction 0.82 Co 0.05 Mn 0.11 Al 0.02 The (OH)2 precursor was mixed with Li2CO3 so that the Li / Me (Ni, Co, Mn, Al) molar ratio was 1.03, and then heat-treated at 800°C for 10 hours in an oxygen atmosphere to produce LiNi 0.82 Co 0.05 Mn 0.11 Al 0.02 A positive electrode active material containing O2 lithium composite transition metal oxide was produced.

[0132] [Table 1]

[0133] [Experimental Example 1: Average particle size] D50 is defined as the particle size at 50% of the particle size distribution and was measured using a laser diffraction method.

[0134] [Experimental Example 2: Crystal size of primary particles] The samples were measured using a Bruker Endeavor (CuKα, λ = 1.54 Å) equipped with a LynxEye XE-T position sensitive detector at FDS 0.5°, over the 2θ range of 15° to 90° with a step size of 0.02° and a total scan time of 20 min.

[0135] The measured data were subjected to Rietveld refinement, taking into account the charge (+3 for metals at transition metal sites, +2 for Ni at Li sites) and cation mixing from each site. For crystal size analysis, instrumental broadening was considered using the Fundamental Parameter Approach (FPA) implemented in the TOPAS program manufactured by Bruker, and the entire peak in the measurement range was used for fitting. Peak morphology was fitted using only the Lorenzian contribution in the First Principle (FP) of the peak types available in TOPAS, and strain was not considered. The crystal size results are shown in Table 1.

[0136] [Experimental Example 3. Measurement of true density] The samples were measured using a Bruker Endeavor (CuKα, λ = 1.54 Å) equipped with an X LynxEye XE-T position sensitive detector, with FDS 0.5°, 2θ 15° to 90°, step size 0.02°, and a total scan time of 20 min. Based on the measured data, true density = (weight of elements in a unit cell, g) / (unit cell volume, cm 3 ) was calculated.

[0137] [Experimental Example 4. High temperature life characteristics of coin-type full cells] The lithium secondary battery full cells prepared as described below using the positive electrode active materials prepared in Examples 1 and 2 and Comparative Example were charged at 45° C. in CC (constant current)-CV (constant voltage) mode at 0.7 C to 4.25 V, and discharged at a constant current of 0.5 C to 2.5 V, and then charged and discharged 300 times to measure the capacity retention and evaluate the life characteristics. The results are shown in FIG. 1 and Table 2.

[0138] [Table 2]

[0139] [Experiment Example 5: Measurement of DCR resistance for each SOC] Leave A coin-type full cell was fabricated, left for 10 hours, and then charged and discharged in formation (0.2C / 0.2C). After charging to 4.25V, the SOC was set based on the discharge capacity measured during formation, and a discharge pulse (1.0C pulse for 10 seconds) was applied to calculate the resistance value at each SOC.

[0140] For DC-IR calculation, DCIR=(V0-V1) / I Calculations were made using (V0 = voltage before the pulse, V1 = voltage 10 seconds after the pulse, I = applied current).

[0141] The results are shown in FIG. 2, Tables 2 and 3.

[0142] [Table 3]

Claims

1. at least one secondary particle comprising an agglomerate of a primary macroparticle; The primary macroparticles have an average particle size (D50) of 2 μm or more; the ratio of the average particle size (D50) of the primary macroparticles to the average crystal size of the primary macroparticles is 8 or more; The secondary particles have an average particle size (D50) of 3 μm to 10 μm, and a true density (crystal density) of 4.74 g / cc or more.

2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the primary macroparticles have an average crystal size of 200 nm or more.

3. 3. The positive electrode active material for lithium secondary batteries according to claim 1, wherein the ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary large particles is 2 to 4.

4. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the secondary particles contain a nickel-based lithium transition metal oxide.

5. The nickel-based lithium transition metal oxide is Li a Ni 1-x-y Co x M1 y M2 w O 2 5. The positive electrode active material for a lithium secondary battery according to claim 4, comprising: (1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M1 is at least one selected from the group consisting of Mn and Al, and M2 is at least one selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo).

6. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the positive electrode active material for a lithium secondary battery contains at least one of zirconium, yttrium, and strontium as a sintering additive.

7. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein a surface of the positive electrode active material for a lithium secondary battery is coated with a boron-containing material.

8. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein a surface of the positive electrode active material for a lithium secondary battery is coated with a cobalt-containing material.

9. A positive electrode for a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery according to claim 1.

10. A lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to claim 1.

11. A method for producing a positive electrode active material for a lithium secondary battery according to claim 1, (S1) mixing a nickel-based transition metal oxide precursor having a tap density of 2.0 g / cc or less with a lithium precursor and primarily baking the mixture; (S2) a step of secondarily firing the primary fired product; Through the primary and secondary firing, a positive electrode active material for a lithium secondary battery is prepared, the positive electrode active material including at least one secondary particle including an aggregate of a primary large particle, The primary macroparticles have an average particle size (D50) of 2 μm or more; the ratio of the average particle size (D50) of the primary macroparticles to the average crystal size of the primary macroparticles is 8 or more; The secondary particles have an average particle size (D50) of 3 μm to 10 μm, and a true density (crystal density) of 4.74 g / cc or more.

12. The method for producing a positive electrode active material for a lithium secondary battery according to claim 11, wherein the temperature of the primary baking is 780°C to 900°C.

Citation Information

Patent Citations

  • Single-crystal lithium nickel cobalt manganese oxide ternary positive electrode material and low-temperature sintering preparation method thereof

    CN111129448A

  • Ternary positive electrode material, preparation method thereof and lithium ion battery

    CN111200120A

  • High-performance lithium-ion battery materials

    JP2009536438A

  • Positive active material for rechargeable lithium battery, method of manufacturing the same, and positive electrode and rechargeable lithium battery including the same

    JP2015023021A

  • Positive electrode active material for lithium secondary battery and method for producing same

    JP2020515010A